Silent Songs and Sounds of Ceremony Series - Willis, Steve (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2025)
These images visually address the space between the physical and spiritual. The group title of Silent Songs refers to the space between musical notes, so music can be played and understood. Similarly, these images refer to the space between thoughts–the place of silence where humanity coexists with divinity. It is easy to recognize the similarity of celestial and cerebral thoughts as dot-patterns and star patterns.